2020
DOI: 10.3390/s20205879
|View full text |Cite
|
Sign up to set email alerts
|

A Shape Approximation for Medical Imaging Data

Abstract: This study proposes a shape approximation approach to portray the regions of interest (ROI) from medical imaging data. An effective algorithm to achieve an optimal approximation is proposed based on the framework of Particle Swarm Optimization. The convergence of the proposed algorithm is derived under mild assumptions on the selected family of shape equations. The issue of detecting Parkinson’s disease (PD) based on the Tc-99m TRODAT-1 brain SPECT/CT images of 634 subjects, with 305 female and an average age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The training set was used to build a random forest model and the test set was used to evaluate the performance of the classifier. This 80-to-20% scheme is commonly adopted to evaluate classification performance in the fields of machine learning [21], social science [22], medical science [23], finance [24], and signal processing [25]. In the proposed procedure, because we randomly sampled approximately 80% of the data to learn random forest models from the 2nd to 6th nodes, different classification models may be obtained owing to different sampling results.…”
Section: Discussionmentioning
confidence: 99%
“…The training set was used to build a random forest model and the test set was used to evaluate the performance of the classifier. This 80-to-20% scheme is commonly adopted to evaluate classification performance in the fields of machine learning [21], social science [22], medical science [23], finance [24], and signal processing [25]. In the proposed procedure, because we randomly sampled approximately 80% of the data to learn random forest models from the 2nd to 6th nodes, different classification models may be obtained owing to different sampling results.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies use geometric image features including the length and volume of the segmented striatum [23], shape fitting coefficients [24], [25], isosurfaces [16], and intensity summary statistics [22].…”
Section: B Datscan Classificationmentioning
confidence: 99%
“…It is therefore intriguing that few studies of this problem can be found in the literature. Indeed, projections onto quadratic surfaces have been studied for the 2D and 3D cases, see e.g., [23,22,18]. However, to the best of our knowledge, the extension to an arbitrary dimension has not been pursued, with the exception of the short discussion at the end of [22] and in [27].…”
Section: Introductionmentioning
confidence: 99%